2010
DOI: 10.1074/jbc.m109.032672
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Regulation of Prostaglandin-Endoperoxide Synthase 2 (Ptgs2) Expression in Colonic Mesenchymal Stem Cells

Abstract: We previously found that a population of colonic stromal cells that constitutively express high levels of prostaglandin-endoperoxide synthase 2 (Ptgs2, also known as Cox-2) altered their location in the lamina propria in response to injury in a Myd88-dependent manner (Brown, S. L., Riehl, T. E., Walker, M. R., Geske, M. J., Doherty, J. M., Stenson, W. F., and Stappenbeck, T. S. (2007) J. Clin. Invest. 117, 258 -269). At the time of this study, the identity of these cells and the mechanism by which they express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 71 publications
2
49
0
Order By: Relevance
“…The purpose would be to find and utilize MSCs with the highest VEGF expression. For example, global gene analysis of MSCs isolated from mice showed that cMSCs produce more Vegf mRNA than bone marrow MSCs (34). It is likely that cMSCs produce other proangiogenic or prohealing factors that work via other pathways, but our results suggest that MSCs are most effective for mucosal wound healing when injected intramucosally and that VEGF expression/angiogenesis plays an important part in mucosal repair.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The purpose would be to find and utilize MSCs with the highest VEGF expression. For example, global gene analysis of MSCs isolated from mice showed that cMSCs produce more Vegf mRNA than bone marrow MSCs (34). It is likely that cMSCs produce other proangiogenic or prohealing factors that work via other pathways, but our results suggest that MSCs are most effective for mucosal wound healing when injected intramucosally and that VEGF expression/angiogenesis plays an important part in mucosal repair.…”
Section: Discussionmentioning
confidence: 72%
“…This level of knockdown is relevant, as mice that are heterozygous for Vegf are not viable due to the exquisite dose dependency of VEGF (29). Nontargeting and VEGF shRNA lines maintained cell surface markers consistent with those of cMSCs (Supplemental Figure 17) (34). We found that the minimal number of nontargeting shRNA cMSCs that rescued muscle necrosis in injured Ptgir -/-mice was 3 × 10 5 injected cells ( Figure 6B).…”
Section: Acta2-creermentioning
confidence: 84%
See 2 more Smart Citations
“…Instead, they reported a MyD88-dependent repositioning of Cox-2-expressing stromal cells of unknown identity toward colonic epithelial progenitor cells located at the base of colonic crypts. In a recent study, this group determined that these colonic stromal Cox-2-positive cells are mesenchymal stem cells (38). This repositioning was required to maintain epithelial cell proliferation in response to injury.…”
Section: Discussionmentioning
confidence: 99%